Evaluating the Efficacy of Inhaled Colistin via Two Nebulizer Types in Ventilator-Associated Pneumonia: Prospective Randomized Trial - Chung-Chi Huang; Tien-Pei Fang; Chieh-Mo Lin; Chien-Ming Chu; Hsuan-Ling Hsiao; Jui-Fang Liu; Hsin-Hsien Li; Li-Chung Chiu; Kuo-Chin Kao; Chin-Hsi Kuo; Shaw-Woei Leu; Hui-Ling Lin (MDPI AG, 2024)
Backgroud: This prospective randomized trial evaluated the clinical efficacy of inhaled colistin administered through two distinct nebulizer types, a vibrating mesh nebulizer (VMN) and a jet nebulizer (JN), in the treatment of ventilator-associated pneumonia caused by multidrug-resistant bacteria. In addition, an in vitro model was used to determine the optimal delivery of colistin. Method: Thirty-two patients prescribed intravenous (IV) colistin inhalation were randomized to receive either a VMN (n = 17) or a JN (n = 15), then compared to the control group (IV alone) over a 7-to 10-day period. The primary endpoint was the clinical pulmonary infection score (CPIS), and the secondary endpoints were the Sequential Organ Failure Assessment (SOFA) score, Acute Physiology and Chronic Health Evaluation (APACE) score, and duration of ventilator use. Results: Results from in vitro testing demonstrated that VMN delivered a significantly higher colistin dose than JN (35.68 ± 3.55% vs. 23.56 ± 3.31%; p < 0.001) when positioned at the humidifier inlet. Compared to the IV alone group, the IV with inhalation group yielded significant improvements in CPIS, SOFA score, and APACHE score on day 7; nevertheless, clinical outcomes between the two nebulizers were statistically indistinguishable. Conclusions: In conclusion, although VMN delivers a higher dose in vitro, both nebulizers yielded comparable clinical outcomes. This study was registered at US Clinical Trial Registration (NCT04633317).